MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SD NEGERI 244 PALEMBANG - Indah Amallia; Yenny Anwar; Inda Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to see and know the improvement of Student Learning Outcomes through Audio Visual Learning Media in Pancasila Education Learning in Class IV SD Negeri 244 Palembang. This research is a research with the type of Classroom Action Research (PTK), Classroom Action Research (PTK) can be defined as a form of study or scientific activity and method conducted by teachers / researchers in the classroom by using actions to improve learning processes and outcomes. The purpose of Classroom Action Research (PTK) is to improve the quality and learning outcomes practically. The population and sample of this study were students of class IV.B SD Negeri 244 Palembang with 37 students. Data collection techniques using tests and documentation. Instruments to measure learning outcomes using multiple choice questions as many as 10 questions. In the pre-cycle obtained an average value of 39.71 with a percentage of completeness of 5%, in the cycle obtained an average value of 47.29 with a percentage of completeness of 19%, and when the application of cycle II increased with an average of 89.45 with a percentage of completeness of 95%. Thus it can be concluded that there is a significant increase in student learning outcomes when given Audio Visual media treatment in class IV SD Negeri 244 Palembang